Mitigating Emissions Associated With the Production of Traded Goods - Quirapas, Dan André (Animo Repository, 2021)
The environmental impact of international trade is a concerning issue in the fight against climate change. Trade liberalization—combined with globally fragmented environmental policies—is often associated with the formation of pollution havens. This is because trade enables emissions leakages, which is defined as the outsourcing of emissions-intensive production to countries with weaker environmental regulations. Therefore, literature on this subject has suggested that a globally coordinated policy response is necessary to mitigate the impact of trade on climate change (Aichele & Felbermayr, 2012; Ben-David et al., 2020; Felbmermayr & Peterson, 2020). However, some studies have found that unilateral policy actions have no tangible effect on the volume of emissions associated with trade and, in some cases, the reduction of emissions volume associated with trade (Baylis et al., 2014; Kumar & Prabkahar, 2016; Hoekstra et al., 2016). This policy brief aims to provide insights on unilateral or multilateral actions countries can take to mitigate the impact of embodied emissions associated with the production of traded goods.